Histological Effects of the Antibiotic Gentamicin on the Ovarian Tissue of Female White Laboratory Rats - Saja. A. Mazher; Atyaf. S. Hussein; Zahraa. H. Abdulateef (International Journal of Antibiotics, 2025)
This study aimed to evaluate the histological alterations induced by Gentamicin in the ovarian tissue of white laboratory rats. A total of 12 adult female rats were used and randomly divided into two groups, with each group consisting of six animals. The experimental group received Gentamicin at a dose of 120 mg/kg body weight administered as an injection once daily, while the control group received an equivalent volume of normal saline under the same conditions. The treatment continued for a predetermined period to allow assessment of both acute and progressive tissue changes. After the treatment period, all animals were humanely euthanized, and the ovaries were carefully dissected, fixed in 10% formalin, processed, and sectioned for detailed histological examination using routine hematoxylin and eosin staining. Histopathological analysis revealed significant ovarian damage in the Gentamicin-treated group, demonstrating a clear deviation from the normal ovarian architecture observed in the control group. Key microscopic changes included marked cytoplasmic vacuolization, nuclear pyknosis, and noticeable disorganization of both granulosa and theca cell layers surrounding developing follicles. Oocyte shrinkage was also evident, indicating severe degenerative changes affecting folliculogenesis. In addition to these cellular alterations, prominent vascular congestion and stromal edema were identified, suggesting compromised microcirculation within the ovarian stroma. The presence of inflammatory cell infiltration further supported the occurrence of tissue injury and an ongoing inflammatory response. These structural and cellular alterations collectively suggest that Gentamicin induces oxidative stress–mediated follicular degeneration, leading to impaired oocyte maturation and potentially reduced fertility. The observed damage may be attributed to the drug’s known nephrotoxic and cytotoxic properties, which can generate reactive oxygen species (ROS) and disrupt normal cellular homeostasis. Such oxidative imbalance may interfere with hormonal regulation, follicular development, and stromal integrity. Overall, the findings underscore the potential reproductive toxicity of Gentamicin and highlight the need for cautious therapeutic use, particularly in females of reproductive age. Further studies are recommended to explore mechanistic pathways, dose-dependent effects, and possible protective agents that may mitigate Gentamicin-induced ovarian injury.
Keywords: Follicular Degeneration; Gentamicin; Ovarian Histology; White rats; animal; antibiotic; granulosa